PENGARUH PEHAMAN LITERASI KEUANGAN, KEMUDAHAN DIGITAL PAYMENT DAN INKLUSI KEUANGAN TERHADAP KINERJA UMKM DIKOTA BANDAR LAMPUNG - Nuzulya Pahlawi; Maria Septijantini Alie; Hasbullah Hasbullah; Armalia Reny; Desmon Desmon; Yudhinanto CN; Susi Indriyani (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Purpose: This study aims to determine the effect of Good Corporate Governance on the Financial Performance of BUMN Companies listed on the Indonesia Stock Exchange in 2019-2023. Methodology/approach: This type of research uses quantitative methods. This study used 70 researchs samples. There are two variables in this study, namely: 4 (four) independent variables (X1, X2, X3, X4) and 1 (one) dependent variable where institutional leadership (X1), board of directors (X2), board of commissioners (X3) and audit committee (X4) as independent variables and financial performance (Y) as the dependent variable. Results/findings: Based on data analysis, it has been found that the answer to the hypothesis is that institutional ownership, board of directors, board of commissioners, and audit committee simultaneously and partially have a significant effect on financial performance in BUMN companies listed on the Indonesia Stock Exchange in 2019-2023. Limitations: The independent variables in this study are only institutional ownership, board of directors, board of commissioners, and audit committee and the dependent variable isfinancial performance (ROA). The research was only conducted on BUMN companies listed on the Indonesia Stock Exchange. Contribution: Management is expected to pay more attention to Good Corporate Governance in the company in order to create good company value.